2010
DOI: 10.2478/v10029-010-0003-6
|View full text |Cite
|
Sign up to set email alerts
|

European Inclusive Physical Education Training

Abstract: SummaryThe purpose of this presentation is to introduce the outcomes of the project European Inclusive Physical Education Training (EIPET; LLP/LdV/TOI/2007/IRL-502). The project aims to tackle difficulties that arise associated with the inclusion of children with disabilities into general education; and associated current deficiencies in initial and continued physical education teacher training to deal with same. The purpose of this article is to describe job specific functions, which general PE teachers can f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…Including students with disabilities into general physical education (GPE) is currently common practice in most European countries (Klavina, 2008;Kudláček, Ješina, & Flannagan, 2010;Morley, Bailey, Tan, & Cooke, 2005). While the inclusion process has been mandated by international legislation, many barriers have been encountered such as inadequate teacher training and professional development, lack of competence (Rybová & Kudláček, 2013), limited support (Rybová & Kudláček, 2013), large class sizes, and time and administrative demands (Kodish, Hodges Kulinna, Martin, Pangrazi, & Darst, 2006), as well as L. Baloun et al Attitudes of mainstream teachers towards the inclusion of children with special needs in ordinary schools were surveyed by Avramidis and Norwich (2002) who described studies of teachers' attitudes towards inclusion from the review of literature.…”
Section: Introductionmentioning
confidence: 99%
“…Including students with disabilities into general physical education (GPE) is currently common practice in most European countries (Klavina, 2008;Kudláček, Ješina, & Flannagan, 2010;Morley, Bailey, Tan, & Cooke, 2005). While the inclusion process has been mandated by international legislation, many barriers have been encountered such as inadequate teacher training and professional development, lack of competence (Rybová & Kudláček, 2013), limited support (Rybová & Kudláček, 2013), large class sizes, and time and administrative demands (Kodish, Hodges Kulinna, Martin, Pangrazi, & Darst, 2006), as well as L. Baloun et al Attitudes of mainstream teachers towards the inclusion of children with special needs in ordinary schools were surveyed by Avramidis and Norwich (2002) who described studies of teachers' attitudes towards inclusion from the review of literature.…”
Section: Introductionmentioning
confidence: 99%
“…Adapted physical education (APE) lessons customise skills training approaches for school‐aged children with disabilities (Sherrill 2004), but studies have indicated that pedagogical challenges are continually faced by APE teachers (Kudlacek et al . 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Adapted physical education (APE) lessons customise skills training approaches for school-aged children with disabilities (Sherrill 2004), but studies have indicated that pedagogical challenges are continually faced by APE teachers (Kudlacek et al 2010). For example, the use of explicit instructions to augment movement skill development needs to be carefully considered when training children with ID ( Jobling 1994) because of impaired cognitive resources.…”
Section: Introductionmentioning
confidence: 99%
“…Integrace žáků se zdravotním postižením do vyučova-cích jednotek školní TV je aktuálním tématem českého školství a model pro řešení této problematiky dostává v evropských zemích postupným tempem svoji rám-covou podobu (Kudláček, Ješina, Bláha, & Janečka, 2010;Kudláček, Ješina, & Flannagan, 2010;Klavina & Kudláček, 2011).…”
Section: úVodunclassified